Estimación de la relación entre las proteínas plasmáticas de la yegua y los niveles de IgG séricos en otros neonatos de 24 horas de edad (2023)
The level of serum immunoglobulin G in horses is of utmost importance since it gives origin of defense mechanisms mediated by antibodies which bind to antigens specific as those found on the surface of bacteria, in horses the level of Immunoglobulin G is 1000 to 1500 mg/dl, being the immunoglobulin that reaches the highest concentration in the blood. In the case of the mare, the placenta is of the epitheliochorial type, this anatomical condition prevents the correct transfer of immunoglobulins to the fetus during gestation and also serves as a barrier to environmental pathogens. (Carabetta, Fernandez,2016). Foals must ingest an appropriate amount of colostrum in order to acquire a efficient passive immunity since, due to its type of placenta, foals can be born agamaglobulinemic (Jeffcott, 1974). Passive transfer failure (FTP) occurs when there is no good absorption of colostrum throughout the first 24 hours of life or the colostrum does not have the quality or production suitable in the case of first-time or very old mares, this gives rise to a deficiency in the transfer of maternal antibodies especially immunoglobulin G (IgG), which increases the predisposition to infectious diseases and death of foals in his first days of life. (Palomino J, 2021) The decrease in the absorption of immunoglobulins by the foal as As time progresses, it is due to the response of the specialized enterocytes desquamation with pinocytosis capacity and its replacement by more mature cells that are capable of absorb immunoglobulins in the intestine for a limited time, this ranges from the 8 birth until the first 18 to 24 hours of life. (Barrington and Johnson, 2010; Corley and Jokisalo, 2015). Equine neonatal septicemia is the systemic inflammatory response to infection, There is a wide variety of events that can facilitate sepsis in the foal and these are described taking into account maternal and postnatal factors. Maternal factors include difficulty in childbirth, early separation of the 13 placental membranes, placentitis and others forms of illness such as those associated with signs of colic, pneumonia, among others. The Most maternal events that cause septicemia in the foal are related to Acute or chronic ascending placentitis. Postnatal causes are related to possible infection routes. However, there is one major exception, the failure of passive transfer of immunoglobulins (mainly IgG), which is defined as the inadequate transfer of colostral antibodies from the mare to the foal, or as an inadequate absorption of them by part of the neonate. It is believed to be the major cause of predisposition to infections and death of foals in their first days of life (Ospina, 2014). being the major cause of mortality and morbidity in horses in their first seven days of life, this causes great losses economics to the equine industry. The disease and its consequences are reflected as stages progressive processes of the same process, in which the systemic response to the infection can generate a generalized inflammatory reaction in organs distant from the initial injury and induce multi-organ dysfunction or failure. (Arroyave, D.J, 2017).